Terahertz Radiation Modulated by Confinement of Picosecond Current Based on Patterned Ferromagnetic Heterostructures. Issue 9 (15th May 2019) - Jin, Zuanming; Zhang, Shunnong; Zhu, Weihua; Li, Qin; Zhang, Wenjie; Zhang, Zongzhi; Lou, Shitao; Dai, Ye; Lin, Xian; Ma, Guohong; Yao, Jianquan
Abstract : The ultrashort laser excitation of nonmagnetic/ferromagnetic/nonmagnetic (NM/FM/NM) heterostructures is intensively studied as a terahertz (THz) emitter. Herein, the combined spintronic and photonic ultrathin metal heterostructures are exploited to realize actively modulated THz radiation. It is demonstrated that the THz radiation can be mediated coherently through the charge current induced by the inverse spin Hall effect (ISHE) and the built‐in transient current quasi‐simultaneously created within the striped NM/FM/NM heterostructures. The waveforms of THz radiation can be shaped by the charge current confinement effect, including the amplitude modulation and the center‐frequency shift. These findings can be utilized for device‐oriented opto‐spintronics and also extend the established THz emitter to THz modulator. Abstract : An actively modulated THz emitter is developed using a trilayer Pt/CoFeB/W heterostructure patterned with micrometer stripes. The modulation of the THz radiation properties (amplitude, central frequency, and bandwidth) is mainly attributed to the changes in the transient charge current confinement effect. The combined spintronic and photonic ultrathin metal heterostructures can be expected to open a new road for THz optoelectronics.